Utilization of Artificial Intelligence for Customer Service: Phenomenological Study of Luwuk Startups - Emma Triana Sutedy; Yayuk Tri Bunta; Amelia Warda; Sriwanti Belani (IECON: International Economics and Business Conference, 2025)
This study explores the utilization of Artificial Intelligence (AI) in enhancing customer service within digital startups, with a particular focus on DRIVE, a startup based in Luwuk, Indonesia. The rapid integration of AI technologies in business operations has reshaped the dynamics of customer interaction and satisfaction. However, there remains limited qualitative research that captures the lived experiences of customer service personnel in smaller startup environments. Using a qualitative phenomenological approach, data were collected through semi-structured interviews with key informants from DRIVE’s customer service team. The participants were selected using purposive sampling to ensure relevant and rich insights. Data analysis was conducted through thematic analysis, allowing the emergence of key themes related to the implementation, challenges, and perceived benefits of AI in their customer engagement processes. The findings indicate that AI significantly improves response time, supports personalization of service, and reduces repetitive workloads. However, the study also uncovers critical concerns, including limited technical infrastructure, low digital literacy among some staff, and the need for continuous human oversight to maintain customer satisfaction. Participants emphasized that AI should act as a support tool rather than a full replacement for human interaction. This study contributes to the existing body of knowledge by providing an in depth understanding of how AI is operationalized in real startup settings, particularly in underrepresented regions such as Luwuk. The insights derived offer practical implications for startup managers, AI developers, and policymakers in designing more effective AI strategies tailored to local digital ecosystems. Future research could expand the scope to multiple startups and incorporate customer perspectives to enrich the analysis.